Совершенствование маркетинговой деятельности предприятий - Тохтаралиева, А.И. (Культура народов Причерноморья, 2014)
Рассмотрены основные теоретические аспекты проведения маркетинга и роль на
предприятии туриндустрии. Определена необходимость применения маркетинговых стратегий на
предприятии туриндустрии. Рассмотрение внедрения инноваций в маркетинге, их позитивного влияния
на увеличение прибыли и повышение конкурентоспособности. Данные рекомендации могут обеспечить и
эффективность предприятия туристической индустрии и удовлетворить потребности потребителей. Розглянуті основні теоретичні аспекти проведення маркетингу і роль на підприємстві
туріндустрії. Визначена необхідність вживання маркетингових стратегій на підприємстві
туріндустрії. Розгляд впровадження інновацій в маркетингу, їх позитивного впливу на збільшення
прибули і підвищення конкурентоспроможності. Дані рекомендації можуть забезпечити і ефективність
підприємства туристичної індустрії і задовольнити потреби споживачів. The basic theoretical aspects of leadthrough of marketing and role are considered on the enterprise
of turindustrii. The necessity of application of marketings strategies is certain on the enterprise of turindustrii.
Consideration of introduction of innovations is in marketing, their positive influence on an increase arrived
increase of competitiveness. These recommendations can provide and efficiency of enterprise of tourist industry
and to satisfy the necessities of users. The purpose of work is is consideration of marketing activity in a
management a firm. For achievement of the put purpose it is required to decide the followings tasks: it is
research of theoretical bases of marketing; - to develop mechanisms and suggestion on perfection of marketing
activity of firm. Marketing is a type of activity, directed on satisfaction of needs and necessities by means of
exchange [1]. Marketing requires a management. An analysis understand under the management of marketing,
planning, organization and control after the leadthrough of measures, directed on establishment and
maintenance of exchange with having a special purpose buyers for achievement of certain tasks of organization.
We consider that activity of modern firm must be directed on maximization arrived, growth of volumes of sale,
output on new markets. It’s often that at the choice of two analogical commodities, users choose products that
firm which it is trusted and at which good image. Therefore, every tourist enterprise needs to be thoughtful above
producing a good image for users, not sparing facilities, inlaid on advertising and advancement. Result, after the
high-quality advertising will cover the inlaid facilities and will bring in a yet greater return.